DETERMINANTS OF FINANCIAL BEHAVIOR OF SMES IN GRESIK CITY WITH STRUCTURAL EQUATION MODEL (SEM) - Handayani, Anita (International Journal of Business, Law, and Education, 2023)
Small and Medium Enterprises (SMEs) are business activities or businesses that can be done by everyone, as long as the person can manage and develop the business. SMEs also have a role in economic independence, which in turn can lead to national independence. SMEs in running their business will be pursued is related to revenue and profit. The purpose of this study is to analyze the direct effect of education level on the financial behavior of SMEs in Gresik, and the indirect effect with financial literacy as an intervening variable. The results showed that the level of education affects financial literacy and financial behavior, financial literacy affects financial behavior, while for the indirect effect, financial literacy can be a mediating variable for the level of education on financial behavior